2019
DOI: 10.1371/journal.pone.0219352
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and molecular characterization of bacteremia Escherichia coli isolates from newborns in the United States

Abstract: Background Escherichia coli is a major cause of neonatal sepsis. Contemporary antibiotic resistance data and molecular characterization of neonatal E . coli bacteremia isolates in the US are limited. Methods E . coli blood isolates, antibiotic susceptibility data, and clinical characteristics were obtained from prospectively identified newborns from 2006 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 61 publications
6
51
0
2
Order By: Relevance
“…On their side, Cole et al [28], studying 43 bacteremia E. coli isolates from newborns obtained between 2006 and 2016 in Oklahoma, found that ST95 was the most prevalent ST (11.3%) followed by ST131 (9.2%) and ST1193 (3.7%). Cole et al [28] noted that ST95 and ST131 isolates were present throughout the studied years, while ST1193 was only seen in the recent years. Overall, neither ST88 nor ST141 belong to the most prevalent clones in North America.…”
Section: Discussionmentioning
confidence: 99%
“…On their side, Cole et al [28], studying 43 bacteremia E. coli isolates from newborns obtained between 2006 and 2016 in Oklahoma, found that ST95 was the most prevalent ST (11.3%) followed by ST131 (9.2%) and ST1193 (3.7%). Cole et al [28] noted that ST95 and ST131 isolates were present throughout the studied years, while ST1193 was only seen in the recent years. Overall, neither ST88 nor ST141 belong to the most prevalent clones in North America.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the AR phenotype does not exclude the presence of AR genes, which may be expressed in vivo or can be involved in the diffusion and spread of AR genes [25]. However, the rapid emergence of resistant bacteria occurring worldwide attributed to the overuse and misuse of antibiotics, healthy subjects harbor an endogenous E. coli population still sensitive to a wide range of antibiotics, contrary to the pathogenic strains isolated from different clinical specimens [26,27,28]. The scarce relevance of commensal E. coli as an AR carrier disagrees with other studies [29,30,31,32] but is consistent with a recent analysis of metagenomes that investigated AR genes in the gut microbiota of healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…Since complete eradication of pks+ E. coli from the gut microbiome is not feasible to reduce CRC risk [ 11 13 ], we aimed at regulating the genotoxin by using prebiotics, a major regulator of the gut microbiota metabolism [ 14 ]. Prebiotics are fermentable fibers, which include oligosaccharides, that have beneficial effects on intestinal health through the maintenance of mucosal integrity, and most importantly, through the promotion of beneficial bacteria feeding on prebiotics to generate short chain fatty acids [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%